Corporate Social Responsibility, Intellectual Capital, Audit Committee on Firm Performance - Sari, Tyasha Ayu Melynda; Rusmawati, Zeni (Jurnal Akuntansi & Keuangan Unja, 2026)
This study aims to analyze the influence of Corporate Social Responsibility (CSR) and Intellectual Capital, with the Audit Committee as a moderator. This research is a quantitative study with a non-casual approach. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The type of data used in this study is secondary data using annual reports and financial statements for the 2019-2021 period. The sampling technique used a purposive sampling method. Data analysis in this study used multiple regression analysis and interaction test analysis or Moderated Regression Analysis (MRA). The results of the study using multiple linear regression analysis indicate that corporate social responsibility has no effect on firm performance and intellectual capital has a positive and significant effect on firm performance. Moderated regression analysis using the Moderated Regression Analysis (MRA) approach shows that the audit committee weakens the relationship between corporate social responsibility and firm performance, while the audit committee strengthens the relationship between intellectual capital and firm performance. Firm performance is an important indicator for firm owners to assess the effectiveness of management in carrying out their responsibilities as firm managers and as one of the considerations for investors in investing.